In utero exposure to electronic cigarette carriers alters craniofacial morphology. - Ethan Richlak; Logan Shope; Ethan Leonard; Leslie Sewell; Tyler Maykovich; Amr Mohi; Roy A Miller; Matthew W Gorr; Loren E Wold; James J Cray (PLoS ONE, 2025)
Objectives Despite the popularity of electronic nicotine delivery systems (ENDS), there is currently a lack of regulation and consistency regarding the formulation of the e-liquids that undergo combustion in use. The two main constituents of most e-liquids are the humectants propylene glycol (PG) and glycerol (vegetable glycerin, VG). E-liquids consist of a ratio of these two components with PG utilized to increase the "throat hit" effect and VG used to increase visible vapor. As PG-based e-liquids are known to generate more carcinogenic carbonyls and increase the uptake of nicotine, many commercial products have moved toward a more VG-centric formulation to reduce potential harm. The purpose of this study was to test the hypothesis that a common VG-based formulation (30/70 PG/VG) would result in fewer negative effects on craniofacial growth compared to an evenly concentrated formulation (50/50 PG/VG) in the absence of nicotine. Materials and methods Adult breeder mice were utilized to generate in utero ENDS component exposed litters including free air exposure (control), 30/70 PG/VG, and 50/50 PG/VG groups. The resulting pups were assessed at postnatal day 14 for skull morphology. Results Data demonstrate significant reductions in body weight, facial, and cranial dimensions, where there was a significant reduction in growth for the 30/70 PG/VG exposed group. There were no significant differences found between control and 50/50 PG/VG. Conclusions These results suggest the overall movement to a more VG-centric ENDS formulation may not result in reduced profile for health concerns. Further, it suggests that PG/VG are not a harmless carrier and now popular nicotine-free ENDS formulation may not be considered safe for use in pregnant populations.